L’evolució del morfema de cinquena person en català antic: de cantats a cantau. - Badal, Manuel (Scripta, 2022)
The evolution of the 5th person verbal morpheme from -TIS > -ts to -u [w] (CANTĀTIS > cantats > cantau) is a defining feature of Catalan, as it systematically occurs in all 5th person forms of all verbs. The replacement of the ending -ts by -u begins in medieval Catalan and takes a long time to consolidate graphically. In this paper, we analyze, from a volume of Saint Vincent Ferrer Sermons, the evolutionary stage that this person presents at the beginning of the 15th century in the verb tenses of indicative, subjunctive and imperative. In addition, we analyze if there are significant chronological differences in the adoption of the innovative forms ending in -u between the three moods. Finally, we compare our results with Wheeler (2012) data to establish whether genre and style affect the distribution of the ending variants